Palmitic acid/polypyrrole composites as form-stable phase change materials for thermal energy storage - Silakhori M.; Metselaar H.S.C.; Mahlia T.M.I.; Fauzi H.; Baradaran S.; Naghavi M.S. (2023)
In this study a novel palmitic acid (PA)/polypyrrole (PPy) form-stable PCMs were readily prepared by in situ polymerization method. PA was used as thermal energy storage material and PPy was operated as supporting material. Form-stable PCMs were investigated by SEM (scanning electron microscopy) and FTIR (Fourier transform infrared spectrometer) analysis that illustrated PA Particles were wrapped by PPy particles. XRD (X-ray diffractometer) was used for crystalline phase of PA/PPy composites. Thermogravimetry analysis (TGA) and differential scanning calorimetry (DSC) were used for investigating Thermal stability and thermal energy storage properties of prepared form-stable PCMs. According to the obtained results the form stable PCMs exhibited favorable thermal stability in terms of their phase change temperature. The form-stable PCMs (79.9 wt% loading of PA) were considered as the highest loading PCM with desirable latent heat storage of 166.3 J/g and good thermal stability. Accelerated thermal cycling tests also showed that form stable PCM had an acceptable thermal reliability. As a consequence of acceptable thermal properties, thermal stability and chemical stability, we can consider the new kind of form stable PCMs for low temperature solar thermal energy storage applications. © 2014 Elsevier B.V. All rights reserved.